Cytological misdiagnosis of high-grade medullary thyroid carcinoma with papillary-like nuclear features: A case report - Mızrak, Ali (The European Research Journal, 2025)
Medullary thyroid carcinoma is an uncommon form of thyroid cancer that arises from the parafollicular C cells. In this case report, a high-grade medullary thyroid carcinoma is discussed, which was initially diagnosed as papillary carcinoma due to the presence of papillary-like nuclear features in the cytological evaluation. A 65-year-old female presented to the ear, nose, and throat department with a palpable neck mass. Based on the cytological features of the fine needle aspiration (FNA), a diagnosis of ’malignant, papillary carcinoma’, (Bethesda category 6) was made. After surgery, histological and immunohistochemical results led to a diagnosis of medullary thyroid carcinoma. Papillary carcinoma-like nuclear features may also be observed in medullary thyroid carcinoma and some cases could be mistakenly interpreted as papillary carcinoma in cytological examination.